Adopsi kecerdasan buatan generatif oleh guru pendidikan jasmani untuk praktik mengajar - Ashari Efendi; Ranti Maulya; Kamarullah; Nopri Abadi Miko; Amrizal (Universitas Tadulako, 2026)
The rapid development of generative artificial intelligence (GenAI) has opened up new possibilities for transforming the nature of teaching; however, empirical data on how physical education teachers can implement and integrate GenAI into their work is still lacking. This study aims to investigate how physical education teachers adopt GenAI in their teaching practices, focusing on their perceptions, usage patterns, and experiences, based on the Unified Theory of Acceptance and Use of Technology (UTAUT). This was conducted using open-ended and closed-ended questionnaires with 66 physical education teachers from Aceh Tengah Regency, Bener Meriah Regency, Aceh Besar Regency, and Banda Aceh City in Indonesia. The UTAUT-based questionnaire, consisting of six constructs and open-ended questions, was used to collect data. Quantitative data were analyzed using descriptive statistics, and qualitative responses were analyzed using thematic analysis. The findings indicate positive adoption of GenAI and, in particular, behavioral intentions and performance expectations. ChatGPT, Gemini, and MetaAI were the most popular, as they are most accessible and widely known. Furthermore, this study identified a three-phase GenAI instructional integration consisting of pre-teaching activities, such as lesson planning, materials development, and assessment preparation; in-teaching activities, such as visual learning support, content organization, and the use of multimedia materials; and post-teaching activities, such as reporting, documentation, and program management. These findings suggest that GenAI is now more of a supplementary technology and has potential as an instructional and administrative tool in the teaching process.